Aplikasi Limbah Cair Pabrik Kelapa Sawit dengan Metoda Biopori terhadap Pertumbuhan Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) Belum Menghasilkan - Joel ' Tambunan; Sampoerno ' '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
To increase the effects of Giving wastewater of oil palm was conducted by the biopory method, waste is included into hole's biopori as food organisms in the soil, organism can change waste become fertilizer which required the young oil palm to growth. This research used completely randomized design (CRD) non factorial consists of 13 treatments, they are S0 = Without treatment, S1 = LCPKS dose of 2.5 liters for 1 tubeunit biopory/plants, S2 = LCPKS dose of 2.5 liter for 2 tube unit biopory/plants, S3 = LCPKS dose of 2.5 liters for 3 tube unit biopory/plants, S4 = LCPKS dose of 2.5 liters for 4 tube unit biopory/plants, S5 = LCPKS dose of 5 liters for 1 tube unit biopory/plants, S6 = LCPKS doses of 5 liters for 2 tube unit biopory/plants, S7 = LCPKS dose of 5 liters for 3 tube unit biopory/plants, S8 = LCPKS dose of 5 liters for 4 tube unit biopory/plants, S9 = LCPKS doses of 7.5 liters for 1 tube unit biopory/plants, S10 = LCPKS doses of 7.5 liter for 2 tube unit biopory/plants, S11 = LCPKS doses of 7.5 liters for 3 tube unit biopory/plants, S12 = LCPKS doses of 7.5 liters for 4 tube unit biopory/plants. Several studies about apllication of liquid waste of oil palm have shown the real influence as growth of height, girth, width of the leaf, and length of the oil palm's leaves varieties Tenera (DXP), marihat 21 month until 24 month immature.   Keywords : LCPKS , holes biopori